(untitled) (Bangladesh Journal of Botany, 2022)
Analysis of phytological and phytoecological aspects of groups of Malva subovata (DC.) Molero & J.M. Monts. in Mounts of Traras was studied. The interpretation was done by correspondence analysis (AFC), the latter makes it possible to seek the affinities which exist between the species or the statements, it aiming to study the dynamics of vegetation and the nature of their evolution in the study environment. This approach allowed to identify groups based on the studied species and specially to know these phytosociological groupings, it presents a broad ecological spectrum. This global treatment allowed one to have an overview of plant formations and to verify that there is indeed an original floral procession. Using phytosociological and phytodynamic data, it was possible to understand the evolution of this species as well as its diversity. In this research, a phytoecological analysis is evident. More than 40 families have been listed. Results showed the importance of the phyto-diversity of the region studied. Bangladesh J. Bot. 51(4): 821-827, 2022 (December)